Indications and Outcomes for Deferred Cytoreductive Nephrectomy Following Immune Checkpoint Inhibitor Combination Therapy: Can Systemic Therapy be Withdrawn in Patients with No Evidence of Disease? - Elisabeth E. Fransen van de Putte; Luna van den Brink; Mohamed A. Mansour; Johannes C. van der Mijn; Sofie Wilgenhof; Johannes V. van Thienen; John B.A.G. Haanen; Ekaterini Boleti; Thomas Powles; Patricia J. Zondervan; Niels M. Graafland; Axel Bex (European Urology Open Science, 2023)
Background: Upfront cytoreductive nephrectomy (CN) is no longer the standard of care for patients with metastastic renal cell carcinoma (mRCC) with intermediate or poor prognosis according to the International mRCC Database Consortium categories. Objective: To investigate indications for CN following first-line ipilimumab-nivolumab, and assess management and outcomes for patients achieving no evidence of disease (NED) after CN. Design, setting, and participants: This was a retrospective cohort study among 125 patients with synchronous mRCC who received ipilimumab-nivolumab treatment between March 2019 and June 2022 at four European centres. At one of the four centres, nivolumab was stopped following NED. Outcome measurements and statistical analysis: We measured complete response of metastases (mCR) according to Response Evaluation Criteria in Solid Tumours 1.1; near-complete response of mestastases (mnCR) was defined as a >80% reduction in cumulative metastatic volume. Treatment-free survival (TFS), disease-free survival (DFS), progression-free survival (PFS), and cancer-specific survival (CSS) were determined. Results and limitations: At median follow-up of 25 mo, 23/125 patients (18%) had undergone deferred CN. Of 26 patients (21%) with mCR or mnCR, 19 (73%) underwent CN to achieve NED, of whom 11 (58%) discontinued nivolumab, with median TFS of 21 mo. For patients who continued (n = 8, 42%) versus discontinued nivolumab following NED, 2-yr DFS was 83% versus 60% (p = 0.675) and 3-yr CSS was 100% versus 70% (p = 0.325). Four patients underwent CN because of a dissociated response of the primary tumour and were still alive at median follow-up of 5 mo. Conclusions: CN can result in NED, durable DFS, and substantial time off systemic therapy. More collaborative data are required to ascertain the benefits of treatment discontinuation versus oncologic safety. Patient summary: In our study using real-world data, 18% of patients treated with immunotherapy underwent deferred kidney surgery. The majority were free of disease after 3 years. Half of the patients who stopped immunotherapy after surgery have been off therapy for 21 months or longer. Larger studies are needed to investigate the effect of kidney surgery and discontinuation of immunotherapy on survival.